PRINCIPLES OF REPRESENTING POLYSEMANTIC LEXEMAS AS HEADWORDS IN THE "EXPLANATORY DICTIONARY OF THE UZBEKISTAN LANGUAGE" (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the principles of giving polysemantic lexemes, which play an important role in Uzbek linguistics, as headwords in explanatory dictionaries. In particular, the specific features of giving types of headwords - homonyms, synonyms and paronyms - in the dictionary structure are highlighted, depending on the form and meaning of the headword.